Heterogenised C-scorpionate iron(II) complex on nanostructured carbon materials as recyclable catalysts for microwave-assisted oxidation reactions - Sónia A. C. Carabineiro (2018)
The C-scorpionate iron(II) complex [FeCl2(Tpm)] [Tpm=(3)-HC(C3H3N2)(3)] (1) was immobilized on five different nanostructured carbon materials (nanodiamonds, graphene nanoplatelets, graphene oxide, reduced graphene oxide, and nanohorns) to produce active, selective, and recyclable catalysts for alkane and alcohol oxidations. The heterogenized systems (including the first ever reported complexes supported on carbon nanohorns) exhibited good activity concomitant with rather high selectivity to the formation of ketone alcohol (KA) oil (cyclohexanol and cyclohexanone mixture, yields up to 29%) from microwave-assisted oxidation of cyclohexane, and allowed their easy recovery and reuse, at least for five consecutive cycles maintaining 90.3% of the initial activity. Moreover, the functionalized nanodiamond supports (used for the first time as supports for iron complexes) were also able to effectively (yields up to 97%) catalyze the microwave-induced oxidation of 1- and 2-phenylethanol to acetophenone and 2-phenylacetaldehyde, respectively, and could be reused for seven consecutive cycles without losing catalytic activity.